Value Based Quality Budgeting Model (Excellence Model for IT Industry) - Sharma, Sushil (Journal of Commerce and Trade, 2008)
Quality has emerged as the most important factor that distinguishes a product from its mere utility value to brand that gives competitive edge over rival products. The fundamental idea here is to understand the value of quality in any product/service the IT industry provides. Researching this, the author has extruded the ‘Value-Based Quality Budgeting Model’. Cycle tier from financial management perspective.